Radioactivity in the Marine Environment: Uranium‐Thorium Decay Series. Issue 1 (27th December 2018) - Benitez‐Nelson, Claudia R.; Buesseler, Ken; Dai, Minhan; Aoyama, Michio; Casacuberta, Núria; Charmasson, Sabine; Johnson, Andy; Godoy, José Marcus; Maderich, Vladimir; Masqué, Pere; Moore, Willard; Morris, Paul J.; et al.
Abstract : Natural and anthropogenic radionuclides are used to study a suite of environmental processes. Yet their applications in aquatic systems are hindered by a general lack of knowledge regarding the underlying concepts of radioactivity, the occurrence of radionuclides in ecosystems, and the equations used to describe their decay mechanisms in environmentally applicable ways. The goal of this lecture is to provide upper level undergraduate and graduate students with a basic understanding of how the naturally occurring uranium‐thorium radioactive decay series can be used to address a range of environmentally relevant questions in marine systems. The lecture begins with a brief introduction to uranium‐thorium series decay patterns and their distribution in the marine environment. The remaining lecture focuses on four case studies that cover a range of applications where uranium‐thorium series radionuclides are used and includes: scavenging, air‐sea gas exchange, tracing groundwater, and sedimentation/age dating. This lecture is the second of a four‐part lecture series on radionuclides in the marine environment.